The novel HLA‐A*02:625 allele was identified in a Chinese bone marrow donor. (11th June 2018) - Han, Z.‐D.; Zhang, W.; Wang, W.; He, J.; Zhu, F.‐M.
Abstract : HLA‐A*02:625 differs from HLA‐A*02:06:01:01 by a single nucleotide substitution at position 806 C>T.